THE DIAGNOSTIC VALUE OF MRI AND ULTRASONOGRAPHY IN POST-TRAUMATIC GONARTHROSIS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Post-traumatic gonarthrosis is one of the degenerative-dystrophic joint diseases that develops as a result of mechanical injuries affecting the osseous, synovial, cartilaginous, and ligamentous structures of the knee joint. Its etiology is often associated with meniscal injuries, cruciate ligament ruptures, or reconstructive processes following surgical interventions. Therefore, early diagnosis and accurate assessment of post-traumatic gonarthrosis play a crucial role in preserving patients' quality of life and timely implementation of conservative and rehabilitative measures. The anatomical structure of the knee joint is complex, requiring advanced imaging modalities to assess its components in a functional state. From this perspective, non-invasive and highly sensitive methods such as magnetic resonance imaging (MRI) and ultrasonography (US) play a pivotal role in detecting inflammation, cartilage degeneration, and injuries to the meniscus and cruciate ligaments within the joint. MRI provides high-resolution, contrast-based, three-dimensional visualization of intra-articular structures, making it a highly effective tool in identifying thinning of cartilage, changes in synovial fluid, subchondral sclerosis, and osteophyte formation in post-traumatic conditions. Although ultrasonography offers lower resolution, it remains a rapid, safe, and real-time imaging method, especially useful in early-stage evaluations of joint effusion, synovitis, and soft tissue swelling. When applied in conjunction with clinical and laboratory data, these imaging techniques significantly improve the early detection of post-traumatic gonarthrosis and help prevent its progression. Accordingly, this article aims to scientifically evaluate the diagnostic capabilities, advantages, and limitations of MRI and ultrasonography in the clinical management of post-traumatic gonarthrosis.